ANALISIS KANDUNGAN FOSFOR MENGGUNAKAN SPECTROFOTOMETER UV-VIS PADA KACANG HIJAU YANG DIAMBIL DARI PASAR KOTA PEKANBARU - Pangoloan Soleman Ritonga; Sukindro - (LPPM Universitas Muhammadiyah Riau, 2012)
Analysis of phosphorus content in green beans was done. Sampling was conducted with a random method (random) from 3 different markets namely the market of Panam, the market of Arengka and the market of Giant. This study aims to analyze the levels of phosphorus in the green beans in the markets of Pekanbaru. The method used in this study is the UV-Vis spectrophotometer, which measured at a wavelength of 400 nm. Research was conducted at the Laboratory of Pathology, Entomology and Microbiology (PEM) Faculty of Agricultural and animal husbandry Pekanbaru Riau Suska UIN 2010. Based on the results obtained from 3 samples of green beans that were analyzed, the results showed that phosphorus levels in green beans from the market of Arengka is 82.3 mg/10g, from Panam Market is mg/10g 88.05 and market of Giant is 89.63 mg/ 10g. From 3 different markets that phosphorus levels obtained ranged from 82.3 to 89.63 mg/10 gr.